Effect of Sowing Date on the Performance of Two Sesame (Sesamum indicum L.) Cultivars under Irrigation at Kennana, Sudan - Ahmed, Faisal E.; Abdallah, Amna A.; M.Omer, Mohammed (University of Khartoum Journal of Agricultural Sciences, 2025)
The effect of five sowing dates (15/6, 1/7, 15/7, 1/8 and 15/8) on phonology and yield of two sesame cultivars grown under irrigation was studied at Kennana Sugarcane Research Farm during 2001and 2002 seasons. The results showed that plants sown earlier (June sowing) significantly took more days to 50% flowering and physiological maturity than the late-sown plants (August sowing) in both seasons. In contrast, no significant difference between the cultivars was recorded in number of days to 50% flowering. Seed yield and yield components were significantly affected by sowing date. Early-sown plants (mid June) gave 100% and 75% higher seed yield than the late-sown plants (mid August) in the first and the second season, respectively. The higher seed yield of the early-sown plants was associated with high number of capsules, number of seeds per capsule and seed weight. The cultivar Promo significantly exceeded Khidir in seed yield, capsule setting and in number of seeds per capsule particularly in the first season. It can be concluded that the optimum sowing date for sesame under irrigation at Kennana is mid June, and that the cultivar Promo is more promising than the cultivar Khidir